German campaign in Norway. Campaign study no. 2, September 30, 1942. - Military Intelligence Service, War Department (Washington, [D.C.] : Military Intelligence Service, War Department, 1942)
Few campaigns in history have been more complicated or more interesting than the campaign in Norway. Troops and naval units of four nations – Great Britain, France, Norway, and Poland- resisted the German invasion. A vast amount of mercantile and naval tonnage was involved. Transport of troops by sea and by air was accomplished with striking ingenuity. New methods of winter combat in mountainous country were tested and proved sound. The coordination of the German spearhead movements was notable. On the first day of hostilities, the Germans made important landings at six different ports. From all these ports spearheads moved inland simultaneously. From Oslo five spearheads were dispatched; from Trondheim, three. In most areas the Norwegians resisted. To assist them, the Allies subsequently made important landings at Narvik, Namsos, and Andalsnes, and supporting landings elsewhere. The decision in Norway was determined, not by superior valor, but by thorough planning, united leadership, coordinated action, swift execution, and superiority of materiel.